Genotype-by-environment interaction effects on blast disease severity and genetic diversity of advanced blast-resistant rice lines based on quantitative traits - Salleh, Syafiqah Binti; Rafii, Mohd Yusop; Ismail, Mohd Razi; Ramli, Asfaliza; Chukwu, Samuel C.; Yusuff, Oladosu; Hasan, Nor’Aishah (Frontiers in Agronomy, 2022)
Introduction Among the rice diseases, rice blast caused by the pathogen Magnaporthe oryzae is a major threat to the global rice cultivation. This experiment was aimed at investigating the genotype by environment interaction effects on the severity of blast disease and variability of the advanced blast resistant rice lines using quantitative characters. Materials and methods The experiment was laid out in randomized complete block design conducted at three locations. Data were collected on 21 traits which included vegetative, physiological, yield and yield components and were subjected to analysis of variance and variance component analysis. Cluster analysis was authenticated using principal component analysis for genotypes’ classification. Results and discussion All vegetative and yield traits showed highly significant variation among the advanced lines and the check. Seberang Prai showed the highest average yield (5.62t/ha), followed by Tanjung Karang (5.39t/ha) and UPM (4.97t/ha). All the advanced lines showed high resistance to blast disease. Evaluation across the three environments indicated that genotype G3, from MR219 based population, had the highest yield and resistance to blast infection. Genotype G21, from MR263 based population, performed best across the three environments studied and were selected for further breeding programme. The two selected lines, three and four clusters derived from MR219 and MR263 based populations, respectively, were recommended as new lines for further breeding programmes.